Teaching Materials Research: A Hybrid Systematic Literature Review and Bibliometric Analysis (2020-2025) - Elbina Mamla Sa'idah; Edison Edison; Hamdi Pranata (AL-ISHLAH: Jurnal Pendidikan, 2025)
The development of teaching materials is a critical area in educational research, especially amidst increasing demands for innovation, digital integration, and learner-centered approaches. Despite growing interest, a comprehensive mapping of trends and theoretical frameworks in teaching materials research remains limited. This study employed a hybrid approach combining a Systematic Literature Review (SLR) and bibliometric analysis to explore scholarly patterns from 2020 to 2025. A total of 913 Scopus-indexed journal articles were selected based on predefined inclusion criteria. The PRISMA framework guided the SLR process, while VOSviewer was used to visualize keyword co-occurrence, citation networks, and author collaborations. Findings reveal that teaching materials research is increasingly robust, with notable growth from 2020 to 2024. The majority of studies focus on digital and multimedia resources, while areas such as contextual and tailored materials remain underrepresented. Six dominant material types were identified: text-based, digital, multimedia, contextual/authentic, problem-based/case-based, and customized. Indonesia emerged as a leading contributor in publication volume. This study highlights the strong alignment of teaching materials research with constructivist, andragogical, and Universal Design for Learning (UDL) frameworks. The dominance of learner-centered and technology-enhanced materials underscores a paradigm shift in instructional design. Future research should expand into underexplored domains, integrate inclusivity principles, and evaluate instructional impact across diverse learning contexts.